Differential effects of vagus nerve stimulation strategies on glycemia and pancreatic secretions. Issue 11 (8th June 2020) - Payne, Sophie C.; Ward, Glenn; MacIsaac, Richard J.; Hyakumura, Tomoko; Fallon, James B.; Villalobos, Joel
Abstract: Despite advancements in pharmacotherapies, glycemia is poorly controlled in type 2 diabetic patients. As the vagus nerve regulates energy metabolism, here we evaluated the effect various electrical vagus nerve stimulation strategies have on glycemia and glucose‐regulating hormones, as a first step to developing a novel therapy of type 2 diabetes. Sprague–Dawley rats were anesthetized, the abdominal (anterior) vagus nerve implanted, and various stimulation strategies applied to the nerve: (a) 15 Hz; (b) 4 kHz, or 40 kHz and; (c) a combination of 15 Hz and 40 kHz to directionally activate afferent or efferent vagal fibers. Following a glucose bolus (500 mg/kg, I.V.), stimulation strategies were applied (60 min) and serial blood samples taken. No stimulation was used as a crossover control sequence. Applying 15 Hz stimulation significantly increased glucose (+2.9 ± 0.2 mM·hr, p  = .015) and glucagon (+17.1 ± 8.0 pg·hr/ml, p  = .022), compared to no stimulation. Application of 4 kHz stimulation also significantly increased glucose levels (+1.5 ± 0.5 mM·hr, p  = .049), while 40 kHz frequency stimulation resulted in no changes to glucose levels but did significantly lower glucagon (−12.3 ± 1.1 pg·hr/ml, p  = .0009). Directional afferent stimulation increased glucose (+2.4 ± 1.5 mM·hr) and glucagon levels (+39.5 ± 15.0 pg·hr/ml). Despite hyperglycemia resulting when VNS, aVNS, and 4 kHz stimulation strategies were applied, the changes in insulin levels were not significant ( p  ≥ .05). In summary, vagus nerve stimulation modulates glycemia by effecting glucagon and insulin secretions, and high‐frequency 40 kHz stimulation may have potential application for the treatment of type 2 diabetes. Abstract : Blood glucose can be controlled by electrically stimulating the vagus nerve. This approach could be a promising therapy of type 2 diabetes.